Morphological and functional features of the udder of Holstein cows of different constitutions - Z.Sh. Mirsaidova; M.B. Normuminova; R. Kenyaev; J.N.Khudzhamov (International Journal on Orange Technologies, 2021)
The morphological and functional properties of the udder of cattle studied in this experiment have been studied. The fact that the diameter of the udder of cows in the experimental groups was at the level of the requirements of the norm indicates that the cows meet the requirements of milking in the apparatus